Conceptualising energy use and energy poverty using a capabilities framework. (June 2016) - Day, Rosie; Walker, Gordon; Simcock, Neil
Abstract: In this article we conceptualise energy use from a capabilities perspective, informed by the work of Amartya Sen, Martha Nussbaum and others following them. Building on this, we suggest a corresponding definition of energy poverty, as understood in the capabilities space. We argue that such an understanding provides a theoretically coherent means of comprehending the relationship between energy and wellbeing, and thus conceptualising energy deprivation, that makes sense across settings including both the global North and South: a coherence which has previously been lacking. At the same time, it has the flexibility to be deployed in a way that is sensitive to local contexts. Understanding energy use in the capabilities space also provides a means for identifying multiple sites of intervention, including some areas that are currently largely overlooked. We argue that this is advantageous for attempts to address energy poverty in the context of climate change and imperatives for the containment of aggregate energy consumption. Highlights: We apply the capabilities approach of Amartya Sen and Martha Nussbaum to conceptualising why energy is used and needed. We propose a definition of energy poverty based on the capabilities approach. We argue that this understanding integrates approaches to energy poverty from global North and South contexts. The proposed definition of energy poverty is multi-dimensional. This understanding opens new conceptual space for interventions to alleviate energy poverty.